Influencing Factors of Breaking Capacity of Double-Break Vacuum Circuit Breakers - Shengwen Shu; Jiangjun Ruan; Daochun Huang; Gaobo Wu (Institute of Advanced Engineering and Science, 2013)
Using a series arrangement of two vacuum interrupters (VIs) has been proved to be an effective way of developing higher voltage vacuum circuit breakers (VCBs), which are known as double-break VCBs. The uniform distribution of the transient recovery voltage (TRV) across each VI is very critical for the breaking capacity of double-break VCBs. In this paper, the TRV distribution characteristics of double-break VCBs was studied by the synthetic test and the PSCAD/EMTDC simulation based on a vacuum arc interruption model. The results show that the bias of the TRV distribution ratio is caused by the stray capacitance and the imbalanced post arc plasma characteristic in each VI, which is consistent with the theoretical analysis. Moreover, the negative effect of grading capacitors was discussed. The results show that it is advisable to limit the value of grading capacitors to those ranges which can guarantee sufficiently improve the voltage distribution.DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2140